2018
DOI: 10.3390/polym10070700
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Graphene-Perfluoroalkoxy Composite and Thermal and Mechanical Properties

Abstract: Perfluoroalkoxy (PFA) material exhibits perfect corrosion resistance under both acid or alkaline circumstances; thus, steel heat exchangers are being substituted by those made of PFA in high corrosion atmospheres. However, the low thermal conductivity of PFA degrades its heat transfer efficiency. Based on the extremely high heat conductivity of graphene, a novel grapheme-PFA composite was proposed to simultaneously meet the demands of heat transfer and corrosion resistance. Ultrasonic dispersion technology was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Figure 5a shows the in-plane ( λ ‖ ) and through-plane ( λ ⊥ ) TCs of pure PFA and the BNNs–PFA composites. The results indicated that pure PFA had a low TC of 0.26 W m −1 K −1 , consistent with the previous study [3]. When the BNNs content exceeded 5 wt %, the λ ‖ was higher than their λ ⊥ .…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 5a shows the in-plane ( λ ‖ ) and through-plane ( λ ⊥ ) TCs of pure PFA and the BNNs–PFA composites. The results indicated that pure PFA had a low TC of 0.26 W m −1 K −1 , consistent with the previous study [3]. When the BNNs content exceeded 5 wt %, the λ ‖ was higher than their λ ⊥ .…”
Section: Resultssupporting
confidence: 91%
“…Perfluoroalkoxy (PFA), as a high-performance fluoropolymer with superior chemical resistance, high thermal stability and low dielectric constant, has a strong potential in electronic packaging. Unfortunately, pure PFA has a low thermal conductivity (TC) of approximately 0.27 W m −1 K −1 , [3] providing insufficient heat dissipation for effective thermal management. Therefore, improving the TC of PFA while maintaining its low dielectric property has significant implications for its application in electronics and portable devices.…”
Section: Introductionmentioning
confidence: 99%
“…Afterwards, the GNs–PFA slurry was dried at 120 °C for 24 h in a vacuum oven to remove the residual ethanol. The obtained GNs–PFA powder was put into a mold and heated at 400 °C for 1 h. The molten GNs–PFA sample was hot-pressed at 380 °C under a pressure of 15 MPa for 15 min, then cooled to room temperature under the ambient pressure to form bulk composites (see Figure S2 for the details of the hot-pressing system) [33]. Finally, the bulk composites (length × width × height: 30 × 30 × 11 mm 3 ) were cut into many thin sheets (30 × 11 × 1 mm 3 ) along the direction perpendicular to the top surface of the bulk composite.…”
Section: Methodsmentioning
confidence: 99%
“…Because of their excellent mechanical strength and good electrical and thermal properties [1][2][3], carbon nanomaterials such as carbon black, carbon nanotubes, and graphene have been intensely investigated with respect to industrial applications in aircraft and vehicles [4][5][6][7][8][9][10]. Among these materials, graphene is often used as a filler in composites to improve both electromagnetic interference (EMI) shielding and the mechanical, electrical, and thermal properties.…”
Section: Introductionmentioning
confidence: 99%